The Prevalence Of Vector Borne Diseases In Tampin Hospital , Negeri Sembilan - B. Sinniah, Ganga Devi (2018)
Vector-borne diseases are considered important diseases and have greatly impact on the health of humans and animals as well. It was first described in 1877 when lymphatic filariasis was found to be transmitted by mosquitoes from human to human. Malaysia lies in a tropical zone, and often invaded by various vector borne diseases especially mosquitoes which are capable of transmitting diseases like malaria, dengue, filariasis, and Japanese encaphalitis. Vector borne diseases like malaria, filariasis, and dengue are still responsible for the high incidence of morbidity and mortality in many tropical countries, including Malaysia.